The effects of alpha-lipoic acid and creatine supplementation on exercise-induced oxidative stress - Yau, C.-Y.; Lian, Y.-M.; Shen, S.-C. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
This study investigates the effects on the antioxidant system of combining high-intensity training with Cr and ALA supplementation. Oral creatine (Cr) supplementation has been used to enhance athletic performance, to maximize power and speed in sprinting, for example. Oral creatine (Cr) is also used to counter free radicals induced by high-intensity exercise. The effect of combining Cr with ALA (Alpha-lipoic acid) supplementation on exercise-induced oxidative stress is unknown. Summary: High-intensity exercise induced more oxidative stress, which decreased after antioxidant supplementation. Our study concludes that serious swimming training causes an increase in oxidative stress like general land exercise and the exercise load may be is a real fact but Cr dietary. The effects of combining Cr and ALA supplementation in swimmers may have a positive effect on exercise-induced oxidative stress.